Actomyosin contractility-dependent matrix stretch and recoil induces rapid cell migration - William Y. Wang (Nature Portfolio, 2019)
How cells migrate in fibrous tissues is still poorly understood. Here, with synthetic 3D fibre matrices of controlled alignment and stiffness, the authors report that cells in stiff matrices move slowly and continuously, but in softer, deformable matrices cells can rapidly slingshot forward via stretch and recoil of matrix fibres.